A Case of Untreated Myeloid Sarcoma of the Pancreas Head Region: Diagnostic Process of AML Subtyping in an Autoptic Case - Yuki Fukumura; Gentaro Taniguchi; Ai Koyanagi; Yuki Horiuchi; Tomonori Ochiai; Yoko Tabe; Katsuhiro Sano; Yifare Maimaitiaili; Naomi Otsuji; Karin Ashizawa; Takashi Yao (Hindawi Limited, 2021)
This study describes an autopsy case of pancreatic/peripancreatic myeloid sarcoma in a 70-year-old man, initially presenting with obstructive jaundice. Pathologically, diffuse infiltration of round cells containing atypical nuclei with marked cleavage was observed mainly in the pancreas head, peripancreatic lymph nodes, spleen, bilateral lung, and bone marrow. Immunohistochemically, the tumor cells were negative for CD20, CD79a, CD3, CD5, c-kit, CD34, and TdT and positive for myeloperoxidase, CD33, CD68, and CD163. Flow cytometry of the peripheral blood showed underexpression of CD11c and aberrant expression of CD56 in the monocyte subset. The peripheral blood smear showed an increase in monocytes and atypia in neutrophils and monocytes, as well as enlarged platelets and polychromatic erythroblasts. Hence, it was suggested that the myeloid sarcoma was derived from the acute transformation of chronic myelomonocytic leukemia. Myeloid sarcoma is an extramedullary-mass-forming hematologic malignancy that is difficult to diagnose, especially when the initial presentation is a pancreatic mass. However, early diagnosis is important for appropriate therapy. Although bone marrow examination could not be performed because of the patients' severe condition, the pathological specimen obtained with autopsy helped subtype the patient's leukemia. The immunohistochemical features of this case merit attention.